Moral reputation and political selection in a decentralized democracy: Theory and evidence from India - Prasenjit Banerjee; Vegard Iversen; Sandip Mitra; Antonio Nicolò; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
What motivates individuals to become politicians? This is an important question in decentralized democracies, where local politicians play a key role in public goods provision. However, and in emerging economies, bureaucratic hurdles and administrative failures introduce uncertainty about the returns to a politician's effort towards public goods provision. This paper presents a theoretical enquiry of political selection in the presence of such uncertainty. When individuals differ in their concern for reputation, our model predicts that politicians' effort is increasing in their reputation concern. With uncertainty about the public goods production (and thus reputational) returns to politician effort, our model also predicts that reputation-concerned individuals are more reluctant to join politics than those who worry less about their perceived moral stature. Using data from lab-in-the-field experiments in rural India with local politicians and non-politician participants, we find support for the main predictions of our model.
Keywords: H11; D64; O12; 330; politicians; experiments; intrinsic motivation; reputation; India